Hubungan antara Pengetahuan Orang Tua tentang Game Edukasi dengan Minat Penggunaannya pada Anak - Aswan, Dedy (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study investigates the relationship between parental knowledge of educational games and children's interest in using them. Utilizing a descriptive quantitative method with a survey of 85 parents in Makassar, South Sulawesi, it was found that parental knowledge significantly and positively correlated (r = 0.42, p < 0.001) with children's interest in educational games. Parental knowledge explained 18% of the variance in children's interest. While most parents demonstrated a moderate level of knowledge (62%), their proficiency in game selection criteria (40%) and guidance strategies (45%) remained relatively low. Children's interest, conversely, was notably high (average score 72.8), particularly in enthusiasm and initiative. These findings underscore the crucial role of parental knowledge as a catalyst in optimizing the utilization of educational games, emphasizing the need for more targeted digital literacy programs for parents to effectively select and guide their children in the digital environment.tua dalam memilih dan mendampingi anak dalam lingkungan digital.